23.0k views
3 votes
How do I solve 0=-2/3x^(-5/3)+8/3x^(-2/3)?

1 Answer

4 votes

Answer: The solution of the given equation is
(1)/(4).

Step-by-step explanation:

The given equation is,


(2)/(3)x^{ -(5)/(3)} +(8)/(3)x^{ -(2)/(3)}=0

It can be written as,


\frac{2}{3x^{ (5)/(3)}} +\frac{8}{3x^{ (2)/(3)}}=0


\frac{8x^{(5)/(3)}-2x^{(2)/(3)}}{3x^{(7)/(3)}}=0


8x^{(5)/(3)}-2x^{(2)/(3)}=0


2x^{(2)/(3)}(4x-1)=0

Equate each factor equal to 0. Then we get,


x=0 and
(1)/(4)

Since the power of x is in negative, so the equation is not defined for x = 0.

Therefore the only solution of the given equation is
(1)/(4).

User Meny
by
5.8k points